Correlation between Sphenoclivus angle and Gnathic angle with age and gender in Iranian population using CT-Scan - Hassanzadeh, Gholamreza; Moshkdanian, Ghazaleh; Gholaminejhad, Morteza; Poorhassan, Mahnaz; Ebrahimi, Babak; Habibi, Reza; Pasbakhsh, Parichehr; Rastegar, Tayebeh; Abdi, Mahdad; Yazdooei, Yasmin; et al. (Journal of Contemporary Medical Sciences, 2021)
Objectives: The aim of this study was to assess whether is a reliable correlation between the cranial and gnathic angulations in the Iranian population. Methods: In a cross-sectional study, 140 patients of Tehran University of Medical Sciences hospitals (70 males and 70 females with an age range of 18-60 years) were selected. Sphenoclivus (cranial base) and gnathic angles were calculated for each case. Then, the data were analyzed using SPSS version 22. Results: Statistical analysis showed a relationship between gnathic angle and female (P < 0.05), but no positive relationship was seen between sphenoclivus angle and gender. There was a significant relationship between sphenoclivus angle and age among men. No significant relationship was found between the gnathic and sphenoclivus angles. Conclusion: Sphenoclivus angle has the closest link with age in males. The gnathic angle has also a positive relationship with females. Our findings suggest an independent growth pattern between the sphenoclivus angle and the gnathic angle.